Preparation of MOF / MXene composite membrane and application in antibiotic desalination

By combining ZnBDC-NH2 MOF nanosheets with MXene, a composite membrane with high water flux and retention rate was prepared, which solved the problem of selectivity and permeability of traditional MOF nanosheets in antibiotic desalination applications, and achieved efficient application in the field of antibiotic desalination.

CN119524637AActive Publication Date: 2025-02-28HUNAN UNIV CHONGQING RES INST

Patent Information

Application Number
CN202411786281.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-28
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

Traditional MOF nanosheets have problems with large pore sizes and irregular stacking in antibiotic desalination applications, resulting in limited selectivity and permeability.

Method used

ZnBDC-NH2 MOF nanosheets were combined with MXene to form a uniform and stable suspension through strong hydrogen bonding, and a composite film was prepared by vacuum-assisted self-assembly method to improve the film formation and separation performance of the film.

Benefits of technology

The efficient application of MOF composite membrane in the field of antibiotic desalination was achieved, and the water flux and retention rate of the membrane were improved. The retention rate of antibiotics was 35.18%-97.59%, the separation factor was 1-37.33, and the water permeability flux was 120.38-294.18 Lm-2h-1bar-1.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to a preparation method of an MOF / MXene composite membrane and application of the MOF / MXene composite membrane in the field of antibiotic desalination separation membranes. The ZnBDC-NH2 MOF nanosheet is prepared by mixing 2-amino terephthalic acid and zinc acetate dihydrate, and the ZnBDC-NH2 MOF nanosheet is prepared by mixing 2-amino terephthalic acid and zinc acetate dihydrate. The preparation method comprises the following steps: mixing and dispersing MXene and the ZnBDC-NH2 MOF nanosheets, so as to prepare a colloidal suspension; and uniformly depositing the colloidal suspension on the surface of a substrate by adopting a vacuum-assisted self-assembly technology to form a uniform stacked structure. According to the ZnBDC-NH2 MOF nanosheet composite membrane with the MXene as the intercalation, nanosheets are arranged in order, and the ZnBDC-NH2 MOF nanosheet composite membrane has excellent mechanical strength and relatively high water flux, so that efficient and rapid separation of antibiotic molecules and salts is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical separation, relates to an antibiotic desalting separation membrane, and in particular to a method for preparing a MOF / MXene composite membrane. Background Art

[0002] In recent years, antibiotics (such as chloramphenicol, erythromycin and streptomycin) have played a very important role in chemical and pharmaceutical production due to their simplicity, low cost and efficient antimicrobial action mode. Antibiotics are generally extracted and purified from fermentation broth by specific microorganisms (fungi and bacteria) growing and reproducing in suitable culture media and environmental conditions. In the process of antibiotic production and preparation, a certain amount of inorganic salts must be added to meet the needs of microbial growth and biological activity. Therefore, antibiotic desalination technology has become a key link in the subsequent process. Traditional antibiotic desalination methods include solvent extraction, ion exchange, resin adsorption, plate and frame filtration, electrodialysis, etc. Although the solvent extraction method is mature, its process is complicated, the equipment is complex, and the use of a large amount of organic solvents is involved in the separation process, which is easy to cause serious impact on the environment. In comparison, membrane separation technology has the advantages of high efficiency, energy saving, and simple operation. It is a green and efficient antibiotic desalination method. The separation process has mild operating conditions, does not involve the use of organic reagents, is more environmentally friendly, and has good application prospects in the field of antibiotic desalination.

[0003] Metal-organic frameworks (MOFs) are porous materials formed by self-assembly of metal clusters and organic ligands. They are ideal candidates for preparing two-dimensional layered films because of their highly adjustable pore structure, specific surface area, and specific adsorption capacity for specific molecules. However, traditional MOF nanosheets have problems such as large pore size and irregular stacking, which limits their selectivity and permeability in antibiotic desalination applications. Therefore, it is very important to carry out effective assembly work on these traditional MOF nanosheets to enhance their film-forming properties, improve the regularity of stacking, and improve the efficiency of antibiotic desalination. As a new type of two-dimensional material, MXene has excellent conductivity, hydrophilicity, and abundant surface functional groups. These properties can enhance the stability of MOF in composite materials and improve the separation performance of composite membranes. Summary of the invention

[0004] In view of the existing technology, in order to simultaneously improve the water flux and retention rate of the membrane, this study used ZnBDC-NH 2 MOF nanosheets and MXene are used as assembly units. A MOF / MXene composite membrane is designed and prepared for the field of antibiotic desalination, aiming to use MXene as an intercalation layer to compensate for the ZnBDC-NH 2 Defects in the stacking process of MOF nanosheets are eliminated, thereby achieving efficient application in the field of antibiotic desalination.

[0005] In order to solve the above technical problems, the present invention discloses a method for preparing a MOF / MXene composite membrane. First, a ZnBDC-NH 2 MOF nanosheets, using ZnBDC-NH 2 The unreacted carboxyl groups on the MOF nanosheets and the hydroxyl groups of the MXene formed strong hydrogen bonds to prepare the suspension. Finally, the composite membrane was prepared by vacuum-assisted self-assembly and dried naturally at room temperature to further study the antibiotic desalination and separation performance. This was achieved by the following steps:

[0006] Step 1: ZnBDC-NH 2 Preparation of MOF nanosheets: A certain mass of 2-aminoterephthalic acid is dissolved in a certain volume of DMF and CH 3 CN mixed solution was dispersed by ultrasound at room temperature for 20 minutes until the ligand was completely dissolved and dispersed evenly, which was used as the ligand solution and marked as solution A. 3 CN mixed solution was used as the spacer solution, denoted as solution B; a certain mass of zinc acetate dihydrate was dissolved in a certain volume of N,N-dimethylformamide (DMF) and acetonitrile (CH 3 CN) was dispersed by ultrasound at room temperature for 20 minutes until it was completely dissolved and evenly dispersed, which was used as the metal solution, recorded as solution C; solution A, solution B and solution C were added to the cuvette tube in sequence, and static reaction was carried out at room temperature for 24 hours. After the reaction, a high-speed centrifuge was used to centrifuge at a speed of 2000 rpm for 10 minutes, and then washed with DMF for three times in a row. After freeze-drying, a brown powder was obtained, which was ZnBDC-NH 2 MOF nanosheets;

[0007] Step 2: Preparation of a MOF / MXene composite membrane: Weigh a certain amount of ZnBDC-NH 2 MOF nanosheets and MXene were mixed in a certain proportion and dissolved in an appropriate solvent to form a uniform and stable suspension. The obtained suspension was deposited on a polymer substrate membrane by a vacuum-assisted self-assembly method and dried naturally at room temperature to form ZnBDC-NH with MXene as the intercalation layer. 2 MOF nanosheet composite membrane.

[0008] The method of the present invention, in step 1: the concentration of zinc acetate dihydrate is 2 mg mL -1 -8 mg mL -1 ; The concentration of 2-aminoterephthalic acid is 2 mg mL-1 -8 mg mL -1 .

[0009] The MOF nanosheets include ZnBDC-NH 2 、CoBDC-NH 2 、CuBDC-NH 2 One or more of, preferably ZnBDC-NH 2 MOF nanosheets.

[0010] Weigh a certain amount of ZnBDC-NH 2 MOF nanosheets and MXene are mixed in a certain ratio, and the concentration of the mixed suspension is 8 wt.%-80 wt.%.

[0011] MXene and ZnBDC-NH 2 The mixed suspension of MOF nanosheets is stacked on the surface of a porous polymer substrate membrane, which includes polytetrafluoroethylene, diacetate, triacetate, polyacrylonitrile, polyvinylidene fluoride, polysulfone, polyethersulfone and cellulose.

[0012] This patent invents the preparation of a MOF / MXene composite membrane and its application in the field of antibiotic desalination separation membrane.

[0013] The operating temperature is room temperature, the operating pressure is 1-8 bar, and the antibiotic / salt separation is achieved; the antibiotic is one of tetracycline hydrochloride, chloramphenicol, norfloxacin and the like, and the antibiotic concentration is 0.01 mg L -1 -0.3 mg L -1 The salt is one or more of sodium sulfate, magnesium sulfate, sodium chloride, and potassium chloride, and the salt concentration is 100 mg L -1 -5000 mg L -1 .

[0014] Compared with the prior art, the MOF / MXene composite membrane described in the present invention has a uniform surface, orderly stacking, and certain flexibility and mechanical strength. The nanosheet composite membrane obtained by the present invention is used for antibiotic desalination, showing good separation performance, can intercept larger antibiotics, and smaller salt ions quickly pass through the membrane, with a large water flux and antibiotic / salt separation factor. Among them, the antibiotic retention rate is 35.18%-97.59%, the separation factor is 1-37.33, and the water permeation flux is 120.38-294.18 Lm -2 h -1 bar -1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a surface scanning electron microscope image of film 1 of Example 1.

[0016] Figure 2 This is a scanning electron microscope image of the cross section of membrane 1 of Example 1.

[0017] Figure 3 This is a surface scanning electron microscope image of membrane 2 of Example 2.

[0018] Figure 4 This is a scanning electron microscope image of the cross section of membrane 2 of Example 2.

[0019] Figure 5 This is a surface scanning electron microscope image of film 3 of Example 3.

[0020] Figure 6 This is a scanning electron microscope image of the cross section of membrane 3 of Example 3.

[0021] Figure 7 This is a surface scanning electron microscope image of membrane 4 of Example 4.

[0022] Figure 8 This is a scanning electron microscope image of the cross section of membrane 4 of Example 4.

[0023] Fig. 9 This is a surface scanning electron microscope image of film 5 of Example 5.

[0024] Fig.10 This is a scanning electron microscope image of the cross section of membrane 5 of Example 5.

[0025] Fig.11 is a surface scanning electron microscope image of comparative film 6.

[0026] Fig.12 This is a cross-sectional scanning electron microscope image of comparative film 6.

[0027] Fig.13 It is a performance comparison chart of antibiotic desalination of membranes 1-6.

[0028] Fig.14 This is a schematic diagram of the screening of MOF / MXene composite membrane. DETAILED DESCRIPTION

[0029] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments thereof, but the following embodiments are by no means intended to limit the present invention in any way.

[0030] Example 1: Preparation of a MOF / MXene composite membrane, the steps are as follows:

[0031] Step 1: ZnBDC-NH 2 Preparation of MOF nanosheets: A certain mass of 2-aminoterephthalic acid was dissolved in a certain volume of DMF and CH3 CN mixed solution was dispersed by ultrasound at room temperature for 20 minutes until the ligand was completely dissolved and dispersed evenly, which was used as the ligand solution and marked as solution A. 3 CN mixed solution was used as the spacer solution, denoted as solution B; a certain mass of zinc acetate dihydrate was dissolved in a certain volume of N,N-dimethylformamide (DMF) and acetonitrile (CH 3 CN) was dispersed by ultrasound at room temperature for 20 minutes until it was completely dissolved and evenly dispersed, which was used as the metal solution, recorded as solution C; solution A, solution B and solution C were added to the cuvette tube in turn, and static reaction was carried out at room temperature for 24 hours. After the reaction, a high-speed centrifuge was used to centrifuge at a speed of 2000 rpm for 10 minutes, and DMF was used to wash continuously for 3 times. After freeze-drying, a brown powder was obtained, which was ZnBDC-NH 2 MOF nanosheets;

[0032] Step 2: Preparation of a MOF / MXene composite membrane;

[0033] Weigh 5 mg of ZnBDC-NH 2 MOF nanosheets and MXene were mixed in a certain ratio to form a uniform and stable suspension with a concentration of 10 wt.% in an appropriate solvent. The suspension was deposited on a polymer substrate by vacuum-assisted self-assembly and dried naturally at room temperature to form a MOF / MXene composite film, which was recorded as film 1. Figure 1 is the surface scanning electron microscope image of membrane 1, Figure 2 is a scanning electron microscope image of a cross section of membrane 1.

[0034] Membrane 1 was used for antibiotic desalination experiment: a nanofiltration cross-flow device was used, the operating temperature was room temperature, the operating pressure was 2 bar, and a mixed aqueous solution of chloramphenicol and sodium chloride was selected. The chloramphenicol retention rate of membrane 1 was 80.72%, the sodium chloride retention rate was 0.27%, the separation factor was 5.17, and the water flux was 121.64 Lm -2 h -1 bar -1 .

[0035] Example 2: Preparation of a MOF / MXene composite membrane. The steps of Example 2 are basically the same as those of Example 1, except that in Step 2, ZnBDC-NH 2 The mass of MOF nanosheets was changed to 10 mg, and finally MXene was used as intercalation layer in ZnBDC-NH 2 MOF nanosheet composite membrane, denoted as membrane 2. Figure 3 is the surface scanning electron microscope image of membrane 2, Figure 4is a cross-sectional scanning electron microscope image of membrane 2.

[0036] Membrane 2 was used for antibiotic desalination experiments: a nanofiltration cross-flow device was used, the operating temperature was room temperature, the operating pressure was 2 bar, and a mixed aqueous solution of chloramphenicol and sodium chloride was selected. The chloramphenicol retention rate of membrane 2 was 97.33%, the sodium chloride retention rate was 0.34%, the separation factor was 37.33, and the water flux was 284.16 Lm -2 h -1 bar -1 .

[0037] Example 3, preparation of a MOF / MXene composite membrane. The steps of Example 3 are basically the same as those of Example 1, except that in step 2, ZnBDC-NH 2 The mass of MOF nanosheets was changed to 15 mg, and finally MXene was used as intercalation layer in ZnBDC-NH 2 The MOF nanosheet composite membrane is denoted as membrane 3. Figure 5 is the surface scanning electron microscope image of membrane 3, Figure 6 is a cross-sectional scanning electron microscope image of membrane 3.

[0038] Membrane 3 was used for antibiotic desalination experiments: a nanofiltration cross-flow device was used, the operating temperature was room temperature, the operating pressure was 2 bar, and a mixed aqueous solution of chloramphenicol and sodium chloride was selected. The chloramphenicol retention rate of membrane 3 was 80.48%, the sodium chloride retention rate was 2.38%, the separation factor was 5.0, and the water flux was 196.8 L m -2 h -1 bar -1 .

[0039] Example 4: Preparation of a MOF / MXene composite membrane. The steps of Example 4 are basically the same as those of Example 1, except that in step 2, ZnBDC-NH 2 The mass of MOF nanosheets was changed to 20 mg, and finally MXene was used as intercalation layer in ZnBDC-NH 2 The MOF nanosheet composite membrane is denoted as membrane 4. Figure 7 is a surface scanning electron microscope image of membrane 4, Figure 8 is a scanning electron microscope image of a cross section of membrane 4.

[0040] Membrane 4 was used for antibiotic desalination experiment: a nanofiltration cross-flow device was used, the operating temperature was room temperature, the operating pressure was 2 bar, and a mixed aqueous solution of chloramphenicol and sodium chloride was selected. The chloramphenicol retention rate of membrane 4 was 80.28%, the sodium chloride retention rate was 4.27%, the separation factor was 4.85, and the water flux was 141.32 Lm -2 h -1 bar -1 .

[0041] Example 5: Preparation of a MOF / MXene composite membrane. The steps of Example 5 are basically the same as those of Example 1, except that in step 2, ZnBDC-NH 2 The mass of MOF nanosheets was changed to 25 mg, and finally MXene was used as intercalation layer in ZnBDC-NH 2 MOF nanosheet composite membrane, denoted as membrane 5. Fig. 9 is a surface scanning electron microscope image of membrane 5, Fig.10 is a cross-sectional scanning electron microscope image of membrane 5.

[0042] Membrane 5 was used for antibiotic desalination experiment: a nanofiltration cross-flow device was used, the operating temperature was room temperature, the operating pressure was 2 bar, and a mixed aqueous solution of chloramphenicol and sodium chloride was selected. The chloramphenicol retention rate of membrane 4 was 78.67%, the sodium chloride retention rate was 4.97%, the separation factor was 4.46, and the water flux was 140.54 Lm -2 h -1 bar -1 .

[0043] Comparative Example 1, ZnBDC-NH 2 The preparation steps of MOF nanosheet composite membrane are as follows:

[0044] Step 1: ZnBDC-NH 2 Preparation of MOF nanosheets: A certain mass of 2-aminoterephthalic acid was dissolved in a certain volume of DMF and CH 3 CN mixed solution was dispersed by ultrasound at room temperature for 20 minutes until the ligand was completely dissolved and dispersed evenly, which was used as the ligand solution and marked as solution A. 3 CN mixed solution was used as the spacer solution, denoted as solution B; a certain mass of zinc acetate dihydrate was dissolved in a certain volume of N,N-dimethylformamide (DMF) and acetonitrile (CH 3 CN) was dispersed by ultrasound at room temperature for 20 minutes until it was completely dissolved and evenly dispersed, which was used as the metal solution, recorded as solution C; solution A, solution B and solution C were added to the cuvette tube in sequence and reacted statically at room temperature for 24 hours. After the reaction, a high-speed centrifuge was used to centrifuge at 2000 rpm for 10 minutes, and DMF was used to wash continuously for 3 times. After freeze-drying, a brown powder was obtained, which was ZnBDC-NH 2 MOF nanosheets;

[0045] Step 2: ZnBDC-NH 2 Preparation of MOF composite membrane: Weigh 10 mg of ZnBDC-NH 2MOF nanosheets form a uniform suspension in an appropriate solvent, and the resulting suspension mixture is stacked on a polymer substrate membrane by a vacuum-assisted self-assembly method, and then naturally dried at room temperature to form ZnBDC-NH 2 MOF nanosheet composite membrane, denoted as membrane 6. Fig.11 is a surface scanning electron microscope image of membrane 6, Fig.12 is a scanning electron microscope image of a cross section of membrane 6.

[0046] Membrane 6 was used for antibiotic desalination experiments: a nanofiltration cross-flow device was used, the operating temperature was room temperature, the operating pressure was 2 bar, and a mixed aqueous solution of chloramphenicol and sodium chloride was selected. The chloramphenicol retention rate of membrane 6 was 62.75%, the sodium chloride retention rate was 0.3%, the separation factor was 2.68, and the water flux was 137.63 Lm -2 h -1 bar -1 .

[0047] By comparing the embodiments and comparative examples, it can be seen that the present invention uses a MOF / MXene composite membrane with a dense surface and no defects. MXene is green and environmentally friendly, widely available and low in cost. It can not only act as a spacer between layers, but also has rich hydroxyl groups and ZnBDC-NH 2 The carboxyl groups of MOF nanosheets form strong hydrogen bonds, which make the nanosheets stacked in an orderly manner and the nanosheet layered film more stable. 2 MOF nanosheet stacking membrane has significantly improved separation performance. Fig.13 This is a comparison chart of the antibiotic desalination performance of membranes 1-6. Fig.14 This is a sieving mechanism diagram of MOF / MXene composite membrane for antibiotic desalination.

[0048] Although the present invention has been described above in conjunction with the accompanying drawings, the present invention is not limited to the above-mentioned specific embodiments. The above-mentioned specific embodiments are merely illustrative and not restrictive. Under the guidance of the present invention, ordinary technicians in this field can make many modifications without departing from the purpose of the present invention, which are all within the protection of the present invention.

Claims

1. Preparation of a MOF / MXene composite membrane and its application in antibiotic desalination, the main features of which are: preparing high aspect ratio ZnBDC-NH2 MOF nanosheets, and making a suspension with MXene, and using a vacuum-assisted self-assembly method to prepare a ZnBDC-NH2 MOF nanosheet composite membrane with MXene as an intercalation layer, the surface of the composite membrane is tightly regular and orderly stacked. The composite membrane is prepared according to the following steps: Step 1: Preparation of ZnBDC-NH2 MOF nanosheets: A certain amount of 2-aminoterephthalic acid was dissolved in a certain volume of a mixed solution of DMF and CH3CN, and ultrasonic dispersion was performed at room temperature for 20 minutes until the ligand was completely dissolved and evenly dispersed, which was used as a ligand solution and marked as solution A; a certain volume of a mixed solution of DMF and CH3CN was used as a spacer solution and marked as solution B; a certain amount of zinc acetate dihydrate was dissolved in a certain volume of a mixed solution of N,N-dimethylformamide (DMF) and acetonitrile (CH3CN), and ultrasonic dispersion was performed at room temperature for 20 minutes until it was completely dissolved and evenly dispersed, which was used as a metal solution and marked as solution C; solution A, solution B and solution C were added to the cuvette tube in turn, and static reaction was carried out at room temperature for 24 hours. After the reaction, a high-speed centrifuge was used to centrifuge at a speed of 2000 rpm for 10 minutes, and then washed with DMF for 3 consecutive times, and a brown powder was obtained after freeze drying, which was ZnBDC-NH2 MOF nanosheets; Step 2: Preparation of a MOF / MXene composite membrane: A specific volume of MXene and different masses of ZnBDC-NH2 MOF nanosheets are mixed in a suitable solvent in a predetermined ratio to obtain a uniform assembly suspension. The suspension mixture is deposited on a substrate membrane using a vacuum-assisted self-assembly method and naturally dried at room temperature to form a MXene-intercalated ZnBDC-NH2 MOF nanosheet composite membrane.

2. A method for preparing a MOF / MXene composite membrane according to claim 1, characterized in that: The concentration of zinc acetate dihydrate is 2 mg mL -1 -10 mg mL -1 ; The concentration of 2-aminoterephthalic acid is 3 mg mL -1 -8 mgmL -1 .

3. The method for preparing a MOF / MXene composite membrane according to claim 1, characterized in that: The MOF nanosheets include one or more of ZnBDC-NH2, CoBDC-NH2, CuBDC-NH2, preferably ZnBDC-NH2 MOF nanosheets.

4. The method for preparing a MOF / MXene composite membrane according to claim 1, characterized in that: ZnBDC-NH2MOF and MXene are mixed in a certain proportion, and the concentration of the suspension after mixing is 8 wt.%-80 wt.%.

5. The method for preparing a MOF / MXene composite membrane according to claim 1, characterized in that: The composite suspension of MXene and ZnBDC-NH2 MOF nanosheets was stacked on the surface of a porous polymer substrate membrane using a vacuum-assisted self-assembly method. The porous polymer substrate membrane includes polytetrafluoroethylene, diacetate, triacetate, polyacrylonitrile, polyvinylidene fluoride, polysulfone, polyethersulfone and cellulose.

6. Application of a MOF / MXene composite membrane prepared according to the method according to any one of claims 1 to 5 in the field of antibiotic desalination.

7. The method according to claim 6, wherein the operation is carried out at room temperature and the operating pressure is 1-8 bar to separate the antibiotic from the salt; the antibiotic is one of tetracycline hydrochloride, chloramphenicol, norfloxacin and the concentration of the antibiotic is 0.01 mg L -1 -0.3 mg L -1 The salt is one or more of sodium sulfate, magnesium sulfate, sodium chloride, and potassium chloride, and the salt concentration is 100 mg L -1 -5000 mg L -1 .

Citation Information

Patent Citations

  • Preparation and application of carboxymethyl cellulose cross-linked ZnBDC MOF nanosheet composite membrane

    CN118925510A

Cited By

  • Preparation and application of MOF (Metal Organic Framework) gel assembled covalent organic framework nanosheet composite membrane

    CN120169192A

  • High-flux nanofiltration membrane for separating antibiotics and salts and preparation method of high-flux nanofiltration membrane

    CN121988179A